To solve the given equations, we can convert the numbers to base 10, perform the arithmetic operations, and then convert the result back to base 2.
First, let's convert the given numbers to base 10:
11base x = 1*10^1 + 1*10^0 = 11
10base y = 1*10^1 + 0*10^0 = 10
10001base 2 = 1*2^4 + 0*2^3 + 0*2^2 + 0*2^1 + 1*2^0 = 17
10base x = 1*10^1 + 0*10^0 = 10
10base 2 = 1*2^1 + 0*2^0 = 2
Now, let's solve the equations in base 10:
11 - 10 = 1
10 - y = 2
y = 10 - 2 = 8
Next, let's convert the result back to base 2:
1base 10 = 1*2^0 = 1
8base 10 = 1*2^3 + 0*2^2 + 0*2^1 + 0*2^0 = 1000base 2
Therefore, the solution to the given system of equations in base 2 is:
x = 1base 2
y = 1000base 2
11base x +10base y=10001base 2
10base x - y=10base 2
Plz solve and leave your ans in base 2
3 answers
what garbage!
11base x +10base y=10001base 2
10base x - y=10base 2
--------------------------------
x+1 + y = 10001
x - y = 10
adding, we get
2x = 10011
I suspect a typo, since we're getting into fractions here.
Also, the question is worded very strangely.
11base x +10base y=10001base 2
10base x - y=10base 2
--------------------------------
x+1 + y = 10001
x - y = 10
adding, we get
2x = 10011
I suspect a typo, since we're getting into fractions here.
Also, the question is worded very strangely.
Apologies for any confusion caused. Let's solve the revised system of equations:
x + y + 1 = 10001base 2
x - y = 10base 2
Subtracting the second equation from the first, we eliminate x:
(x + y + 1) - (x - y) = 10001base 2 - 10base 2
x - x + y + y + 1 - (-y) = 10001base 2 - 10base 2
2y + 1 + y = 10001base 2 - 10base 2
3y + 1 = 10001base 2 - 10base 2
To proceed further, we need to know the base of y. Could you please clarify the base for y?
x + y + 1 = 10001base 2
x - y = 10base 2
Subtracting the second equation from the first, we eliminate x:
(x + y + 1) - (x - y) = 10001base 2 - 10base 2
x - x + y + y + 1 - (-y) = 10001base 2 - 10base 2
2y + 1 + y = 10001base 2 - 10base 2
3y + 1 = 10001base 2 - 10base 2
To proceed further, we need to know the base of y. Could you please clarify the base for y?